Development of Group-Based Cooperative Learning Model to Improve Literacy and Numeracy Learning Outcomes - Marhamah, Marhamah; Noor, Agus Hasbi; Nurhayati, Sri; Rohaeti, Euis Eti; Kartika, Prita (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2026)
This study examines the effectiveness of the STAD (Student Teams Achievement Divisions) cooperative learning model in improving literacy and numeracy outcomes among adult learners in non-formal education settings, specifically in the Paket B program at PKBM Ibnu Ahmad, South Kalimantan. The research aimed to determine whether cooperative learning could enhance students' academic performance, engagement, and motivation in this context. A mixed-methods design was employed, incorporating both quantitative and qualitative data. Pre-test and post-test assessments were conducted to evaluate improvements in literacy and numeracy, while semi-structured interviews and classroom observations provided deeper insights into student and tutor experiences with the cooperative learning model. Paired t-tests were used to analyze the quantitative data, while thematic analysis was applied to the qualitative data. The results revealed significant improvements in both literacy and numeracy skills, with average test scores increasing by 18% in both areas. Qualitative findings highlighted that students felt more engaged and confident, particularly due to the collaborative nature of the learning process. Peer interaction and teacher facilitation were identified as key factors in the success of the intervention. These findings align with previous studies on cooperative learning, which emphasize the positive impact of peer support and collaborative learning on adult education outcomes. The study contributes to the growing body of research on cooperative learning in non-formal education settings by demonstrating the effectiveness of the STAD model in improving adult learners' literacy and numeracy. The findings suggest that cooperative learning can be a valuable tool in non-formal education to enhance engagement, motivation, and academic success. Future research could explore the long-term effects of cooperative learning and its adaptability across different cultural and socio-economic contexts.